Unconventional post-translational modifications in immunological signaling - Mowen, Kerri A; David, Michael (Nature immunology, 2014)
Immune system proteins are subject to numerous post-translational modifications. In this Focus Review, Mowen and David describe the key 'non-conventional' modifications such as acetylation and nitrosylation that affect immunologically-relevant proteins. The activity of a cell is governed by the signals it receives from the extracellular milieu, which are 'translated' into the appropriate biological output, such as activation, survival, proliferation, migration or differentiation. Signaling pathways are responsible for converting environmental cues into discrete intracellular events. The alteration of existing proteins by post-translational modification (PTM) is a key feature of signal-transduction pathways that allows the modulation of protein function. Research into PTMs has long been dominated by the investigation of protein phosphorylation; other PTMs, such as methylation of lysine and arginine residues, acetylation, and nitrosylation of thiol groups and tyrosine residues, have received comparatively little attention. This Review aims to present an overview of these PTMs, with an emphasis on their role in cells of the immune system.